The implications of treaty restrictions of taxing rights on services, especially for developing countries - Faith Amaro; Veronica Grondona; Sol Picciotto (South Centre, 2024)
Taxation of cross-border services has been identified as a high priority issue in the United Nations (UN) negotiations to establish a new global framework for tax. This paper analyses the defects of international tax rules as applied to services, and their exploitation by multinational enterprises (MNEs), focusing on the impact on developing countries. Services have become increasingly important for economic development, but international tax rules favouring delivery by non-residents act as a disincentive to the growth of local services providers, particularly disadvantaging developing countries which are mainly hosts to MNEs. We analyse the restrictions on source taxation of services in tax treaties, particularly those based on the model of the Organisation of Economic Co-operation and Development (OECD), and show that their spread has been accompanied by a widening deficit in services trade of developing countries, while the weakening of their attempts to protect their tax base through withholding taxes has resulted in increasing losses of tax revenue. The paper combines detailed qualitative analyses of tax treaties with quantitative estimates of their effects on trade and tax revenues for services of five developing countries: Argentina, Brazil, Colombia, Kenya and Nigeria. Our analysis suggests that a new approach is needed for taxation of services, breaking with the residence-source dichotomy, and adopting formulary apportionment. This could be based on the standards agreed in the Two Pillar Solution of the OECD/Group of Twenty (G20) project on base erosion and profit shifting (BEPS) and developed now through the UN.
Keywords: 300; Argentina; Base Erosion and Profit Shifting Project (BEPS); Brazil; Colombia; Global Tax; Global Taxation; International Tax; International Tax Cooperation; International Tax Reform; International Taxation; Kenya; Multinational Enterprises (MNEs); Nigeria; Organisation for Economic Co-operation and Development (OECD); Services; Tax; Tax Cooperation; Tax Law; Tax Policy; Tax Reform; Taxation; Taxing Rights; Two Pillar Solution; United Nations (UN)